ANALYSIS OF EXPERIENCE, MANAGEMENT CONTROL SYSTEMS, ORGANIZATIONAL CULTURE, BRUNOUT AND WORK ENVIRONMENT ON HR PERFORMANCE IN SMEs BATIK BAKARAN JUWANA - Devi Astrika Damayanti; Efriyani Sumastuti; Noni Setyorini (Universitas Wahid Hasyim Semarang, 2023)
The research was conducted with the aim of analyzing experience, creativity, responsibility, commitment and work stress on HR performance in Batik Bakaran Juwana SMEs. Data was collected through observation, document analysis, and distributing questionnaires. The data analysis method was carried out using quantitative methods using saturated sampling techniques with 96 employee respondents. The analysis used is multiple regression analysis with the help of the SPSS program. The results showed that first, the experience variable had no positive and significant effect on performance, the second variable creativity had no positive and significant effect on performance, the third variable responsibility had no positive and significant effect on performance, the fourth variable commitment had a positive and significant effect on performance and variables Fifth, work stress has a positive and significant effect on performance.